Association of lower extremity function with nutritional status and number of drugs in patients with chronic heart failure - Morimoto, Yosuke (J Int Med Res, 2020)
OBJECTIVE: This study was performed to investigate the physical performance parameters, including lower extremity function parameters, that may be risk factors for falls in patients with chronic heart failure. METHODS: Seventy patients with stable chronic heart failure were included in this retrospective cross-sectional study. The five-repetition sit-to-stand test (5STS) time, Controlling Nutritional Status (CONUT) score, and number of drugs were assessed. RESULTS: Simple linear regression analysis revealed that the 5STS time was positively correlated with age, the CONUT score, and the number of drugs but was negatively associated with the handgrip force, quadriceps force, and quadriceps muscle thickness. Multiple linear regression analysis showed a significant association between the 5STS time and the CONUT score, quadriceps force, and number of drugs. CONCLUSION: The muscle strength, nutritional status, and number of drugs should be evaluated to prevent lower extremity weakness in patients with stable chronic heart failure.